The roles of locus of causality and buyer attribution in resolution of recurrent supplier‐induced disruptions - Wang, Qiong; Cheng, Li; Craighead, Christopher W.; Li, Julie Juan (Journal of Operations Management, 2022)
AbstractWhile the literature tends to take a dichotomous view of supplier‐induced disruptions, we take a continuum perspective: a buyer perceives a disruption induced by the supplier to varying degrees (i.e., attributing varying levels of responsibility to the supplier), thus affecting the buyer's decisions in switching suppliers. By focusing on the recurrent disruptions, we argue that imputed buyers' attributions of responsibility are characterized by disruptions' recurrent nature and locus of causality—whether the disruptions were repeatedly triggered by recurrent events internal or external to the supplier. Furthermore, while previous studies have identified either buyers' attributions of disruptions or suppliers' justice approaches (to resolve disruptions) as independent factors driving buyers' decisions, we integrate attribution and justice theories and investigate their combined effect—how responsibility attributions affect buyers' switching intentions given suppliers' justice approaches. Using three vignette‐based studies of 705 purchasing managers (supplemented by three robustness check studies), we show that distributive justice attenuates the damaging impact of disruptions triggered by suppliers' internal incidents (internal locus) on buyers' switching intentions, whereas procedural and interactional justice are more instrumental in disruptions triggered by external events (external locus). We conclude by offering substantive guidance for suppliers regarding appropriate actions in preserving the relationship.